Efektivitas Penerapan Model JIGSAW dalam Meningkatkan Hasil belajar Siswa pada Pembelajaran Bahasa Arab di Ma'had Al-Husna Samarinda - Khairy Abusyairi; Yazid Abdillah (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2019)
One important component of learning is the use of appropriate methods. Because the right method will provide a thorough understanding to students, especially cooperative-based methods. The background of the problem with the low learning outcomes of students in Arabic lessons shows that the learning carried out so far has not reached completeness because there are several factors, namely the learning used is still using the lecture method, question and answer questions and assignments. By using the jigsaw learning model is expected to improve learning outcomes. Therefore, the researchers formulated the problems in this study: 1. How is the effectiveness of the application of the jigsaw model in learning Arabic in improving learning outcomes at the Al-Husna Islamic boarding school Samarinda? 2. How to increase the effectiveness of learning outcomes in learning Arabic at the Al-Husna Islamic boarding school Samarinda by using the jigsaw model? The type of research used is Classroom Action Research (CAR), data collection techniques used are tests, observations, and documentation. It can be concluded in this study that the process of learning Arabic by using the application of the jigsaw method can improve student learning outcomes, by meeting the Minimum Completeness Criteria (KKM). The increase in student learning outcomes can be seen from each cycle, in the pre-cycle the average value of student learning completeness is 58 (9 students), with a percentage of 45%, in cycle 1 the average value of student learning mastery is 64 (12 students), with a percentage of 60 %, in cycle 2 the average value of student learning completeness is 70 (17 students), with a percentage of 85%. As well as on the results of observations of teachers and students there is an increase and is carried out well. The researcher uses the demonstration learning method with a more focused focus on involving students directly in the learning process, as evidenced by using the jigsaw model to improve student learning outcomes.